Pengaruh Literasi Keuangan Dan Teknologi Finansial Terhadap Keberlangsungan Usaha UMK Fashion - VIKAWIDIA, ROSITA (Jurnal Pendidikan Ekonomi Indonesia, 2024)
The background of the research is the decline in fashion sector MSMEs in Bandung Regency, which is caused by one of the factors, namely the lack of awareness of the importance of understanding business sustainability. The purpose of this study was to determine the effect of financial literacy and financial technology on the sustainability of fashion sector MSMEs in Bandung Regency. The research method used an explanatory survey, where the questionnaire was used as an instrument and used a Likert scale of 1-5 with a data collection technique of distributing questionnaires to 87 MSMEs in Bandung Regency. The data analysis technique used multiple linear regression for hypothesis testing. The results of the study showed that financial literacy affects the sustainability of fashion sector MSMEs in Bandung Regency, and financial technology does not affect the sustainability of fashion sector MSMEs in Bandung Regency. The implication is to provide support for formulating initiatives regarding the understanding of financial literacy and financial technology that can support business actors in maintaining the existence of their businesses.